PELANGGAN PERGUDANGAN ARCADIA BLOK G20 MERENCANAKANPEMBANGUNAN JARINGAN DISTRIBUSI BARU - Redaksi Tim Jurnal (Energi & Kelistrikan, 2017)
Development economy in the district of Tangerang increased significantly, especially in the areas of industrial. This pushes the level of demand for electrical energy is growing. To meet these needs, it is necessary to mobilize the distribution of electricity to customers as well as possible. In this regard, it takes the addition of new distribution systems in blocks that have not been connected to the distribution network of customers. Before you realize it must be done before the planning process to consider several aspects of the construction, operation, and maintenance of the system. There are some indications that influence the course and outcome of planning such as customer load calculation, load characteristics, network pattern, as well as the voltage drop distribution substation site selection, to obtain a satisfactory planning. Great power to be distributed to every warehouse or factory in Warehousing Arcadia Block G20 is 2.200 VA, 33.000 VA and 66.000 VA with equitable division. The planning process is influenced by the circumstances in carrying out development in accordance with the target of a predetermined time.